Origin and history of the IVS-I-110 and codon 39 [beta]-thalassemia mutations in the Lebanese population - Zahed, Laila (2002)
Using restriction fragment length polymorphisms (RFLPs) and sequence haplotype analysis, we studied the chromosomal background of the β-globin gene in 31 unrelated Lebanese IVS-I-110 or codon 39 (Cd39) subjects, and five normal βA/βA individuals. Our results are compared with those from similar studies in other parts of the Mediterranean in an attempt to provide insights into historical patterns of selection and disease. The great majority of the Lebanese chromosomes with the IVS-I-110 mutation are associated with the RFLP haplotype I and sequence haplotype HT1, which is probably the ancestral structure on which the mutation first emerged. The remainder of the IVS-I-110 alleles are linked to the 5′-subhaplotype 12 RFLP haplotype and/or HTR sequence haplotype. In contrast, in Turkey, IVS-I-110 is associated with six distinct sequence haplotypes and four distinct RFLP haplotypes, suggesting that the mutation probably emerged there. The diversity of sequence haplotypes described in Turkey was probably generated through recombination or gene conversion events with the most frequent βA autochthonous structures. Our data on Lebanese βA chromosomes and Algerian βA chromosomes, along with previously described Turkish βA chromosomes, strengthen this hypothesis. Following its emergence in Turkey, the IVS-I-110 mutation was probably introduced to Lebanon later, by migration or settlements. Cd39 demonstrates a remarkable level of sequence and RFLP haplotype heterogeneity in Algeria, in contrast to its relative homogeneity in Turkish samples. However, its rarity in the Near East, and more specifically in Lebanon, does not allow us to draw any conclusions concerning its origin and gene flow.